CONFLICT STUDIES TOWARDS PEACE STUDIES (CONFLICT RESOLUTION) - Achmad Jaelani; Uus Ruswandi; Mohamad Erihadiana (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2021)
The purpose of writing this article is to study and understand the study of conflict towards peace. This research is motivated by the diversity of ethnicity, ethnicity, language, culture, religion and other differences that cause conflicts between people. The impact and changes that occur after this conflict raise the question of how this conflict can make changes that give birth to various forms and patterns of conflict and provide solutions for resolution. This paper will explain several subjects which will later illustrate the position of conflict studies towards the study of peace. The first part of the writing will discuss the conflict and the dynamics of the conflict. In the second part of the discussion will focus on the relationship between conflicts with solutions to resolution and the variety of conflicts that arise from changes that occur.